Arrhythmias May Hide a Genetic Cardiomyopathy in Left Ventricular Hypertrabeculation in Children: A Single-Center Experience - Irma Battipaglia; Nicoletta Cantarutti; Marianna Cicenia; Rachele Adorisio; Virginia Battista; Anwar Baban; Massimo Stefano Silvetti; Fabrizio Drago (MDPI AG, 2024)
Background. Left ventricular hypertrabeculation (LVHT) is a myocardial disorder with different clinical manifestations, from total absence of symptoms to heart failure, arrhythmias, sudden cardiac death (SCD), and thromboembolic events. It is challenging to distinguish between the benign and pathological forms of LVHT. The aim of this study was to describe the arrhythmic manifestations of LVHT in a large group of pediatric patients and to correlate them with genetic results or other clinical markers. Methods. We retrospectively enrolled 140 pediatric patients with diagnosis of LVHT followed at our Institution from 2013 to 2023. Data regarding family history, instrumental exams, cardiac magnetic resonance, genetic testing and outcomes were collected. Most of them had isolated LVHT (80.7%); in other patients, mixed phenotypes (hypertrophic or dilated cardiomyopathy or congenital heart disease) were present. Results. Arrhythmias were found in 33 children (23.6%): 13 (9.3%) supraventricular tachyarrhythmias; 14 (10%) ventricular arrhythmias (five frequent PVCs (premature ventricular contractions), eight patients with ventricular tachycardia (VT), one ventricular fibrillation (VF)); two (1.4%) sinus node disfunctions; two (1.4%) complete atrio-ventricular blocks (AVB), three (2.1%) paroxysmal complete AVB, one (0.7%) severe I degree AVB. Three patients received an ICD (implantable cardioverter defibrillator). Comparison between LVHT patients with (33 pts) and without (107 pts) arrhythmias as regards genetic testing showed a statistical significance for the presence of class 4 or 5 genetic variants and arrhythmic manifestation (p = 0.037). Conclusions. In our pediatric cohort with LVHT, good outcomes were observed, but arrhythmias were not so rare (23.6%); no SCD occurred.